The Vocabulary Profile in Maritime English Textbooks: A Comprehensive Content Analysis: English - Muhammad Darwin; Andang Saehu; Hanna Sundari (JOEY: Journal of English Ibrahimy, 2026)
This study investigated the vocabulary profile of the Maritime English (ME) textbook Effective Communication at Sea: Mastering SMCP for Maritime Safety and Efficiency (Batu, 2024). Employing a mixed-methods corpus content analysis, a 35,000-token corpus was processed through AntConc to determine lexical frequency across K1, K2, and K3 (off-list/technical) levels, alongside a qualitative semantic audit of polysemic terms and SMCP alignment. Results reveal a distinctive lexical distribution of 72.5% K1, 8.0% K2, and 19.5% K3 tokens, indicating a high technical density optimized for vocational training. Grammatical analysis shows a heavy dominance of nouns (60%) and verbs (30%), reflecting the action-oriented nature of maritime commands. The study confirmed the presence of critical polysemic shifts in high-frequency words (e.g., bridge, draft, head), where meanings deviate drastically from general English. Finally, qualitative evaluation confirms that the textbook achieves high functional integration of IMO-mandated Standard Marine Communication Phrases (SMCP) across both internal and external communication categories. These findings establish a data-driven "70-10-20" vocabulary profile model for the design and audit of vocational maritime instructional materials